"We Really Have to Come Together": Understanding the Role of Solidarity in Asian American College Students' Social Justice Activism and Advocacy - Samuel D. Museus; Gabriel Lê Espiritu; Caitlin Ng (MDPI AG, 2021)
Structural oppression continues to be one of the most pressing problems in U.S. society, and college students have always played a major role in addressing systemic inequities. Yet, much remains to be learned about the experiences of students advocating social justice in higher education, and there is a paucity of research on Asian American students involved in such efforts. This study sought to understand how Asian American undergraduates understand the role of solidarity in social justice work. The authors analyzed interviews with Asian American students engaged in social justice activism and advocacy in the Midwest. Findings show that participants recognized interconnected realities among oppressed communities, centered solidarity in social justice work because of this recognition, and utilized intersectional approaches to integrate solidarity into social justice activism and advocacy. Implications for future research and practice are discussed.